PEMBERDAYAAN KELOMPOK TANI DALAM PENGELOLAAN LIMBAH DAPUR ORGANIK MENJADI PUPUK CAIR DENGAN METODE ECO-ENZYME - Albeta, Sri Wilda; Abdullah, Abdullah; Haryati, Sri; Wulandari, Putri Adita; Pasaribu, Novia Cristi Br (Unri Conference Series: Community Engagement, 2024)
Organic waste such as vegetable and fruit waste that is not managed properly can reduce environmental quality, organic waste can react anaerobically, causing unpleasant odors, vector and rodent breeding and methane gas released into the atmosphere causes global warming which can damage the ozone layer. Organic waste such as vegetable and fruit waste can be used as liquid fertilizer using the Eco-Enzyme method. Eco-Enzyme is a liquid that has a good impact on the environment, a cheap production process, and is also easy to use. The purpose of this community service activity is to increase insight and knowledge about the empowerment and utilization of organic kitchen waste with the Eco-Enzyme method as liquid fertilizer for plants in the Tanjung Gading village farmer group. With this community service activity, the level of knowledge and motivation for making eco-enzyme in farmer groups increased from 18.8% to 100%.